The Marketing Concept in Islamic Perspective: A Literature Review - Mirza Tabrani; Marlizar Marlizar (AFEBI Islamic Finance and Economic Review, 2016)
The objectives of this paper is to review some researches on marketing concept in Islamic perspective. The expected of this review is to provide benefits for related researches in the future. This study uses some review papers, empirical studies and books related to marketing concept in Islamic perspective. The analysis allows identifying interesting points for future research on the topic of marketing concept in Islamic perspective. This paper provides a better understanding on how Islamic perspective on marketing concept. This paper only reviewed concerned articles from Science Direct, Emerald Insight and books. The results of the review showed that the limited studies about the marketing concept in Islamic perspective (Islamic marketing concept). Result of this study is believed to give worth understanding about actual situation in this field of research. It proposed some notions that will stimulate more intensive researches in this field in the future.Keywords: Islamic Perspective, Literature Review, Marketing Concept, Marketing Mix